Difference sequence spaces in $n$-normed spaces defined by Musielak-Orlicz function - Kuldip Raj (Armenian Journal of Mathematics, 2011)
In the present paper we introduced generalized difference sequence spaces combining lacunary sequences and Musielak-Orlicz function $\mathcal{M} = (M_k) $ over n-normed spaces and examine some properties of the resulting sequence spaces.